2017
DOI: 10.1111/jfpp.13338
|View full text |Cite
|
Sign up to set email alerts
|

Water dynamics of turbot flesh during frying, boiling, and stewing processes and its relationship with color and texture properties: Low-field NMR and MRI studies

Abstract: Water dynamics in turbot flesh during frying, boiling and stewing was assessed by nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) techniques. Protons associated with different types of water were distinguished by T 2 relaxation spectra, and significant differen- Practical applicationsWater mobility and distribution can significantly affect turbot flesh physical and biochemical status leading to change the texture, color, tenderness and taste during cooking process. Therefore, it is very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
4
13
0
Order By: Relevance
“…In contrast to the raw fish meat, the enhancement of the cooked mackerel samples exhibited a lower intensity, especially for roasting and Foods 2020, 9, 364 6 of 16 frying groups, which displayed an obvious stripe pattern, suggesting significant change of the proton states during roasting and frying. Similar result was also found in the proton change of MRI with turbot flesh during boiling, stewing and frying processes [23]. Figure 2b clearly shows the relative intensity of T 1 weighted images for mackerel samples, and a significant decrease was observed among the groups of boiling, steaming, roasting and frying.…”
Section: Proton Dynamics During Boiling Steaming Roasting Frying Asupporting
confidence: 81%
“…In contrast to the raw fish meat, the enhancement of the cooked mackerel samples exhibited a lower intensity, especially for roasting and Foods 2020, 9, 364 6 of 16 frying groups, which displayed an obvious stripe pattern, suggesting significant change of the proton states during roasting and frying. Similar result was also found in the proton change of MRI with turbot flesh during boiling, stewing and frying processes [23]. Figure 2b clearly shows the relative intensity of T 1 weighted images for mackerel samples, and a significant decrease was observed among the groups of boiling, steaming, roasting and frying.…”
Section: Proton Dynamics During Boiling Steaming Roasting Frying Asupporting
confidence: 81%
“…Above all, the preliminary PCA showed that the pT 22 parameter could be a candidate in characterizing the water and fat losses as well as enzyme activity of HTS fillets, while the pT 23 parameter could replace the traditional TVB-N, K value, and MDA, although with some limitations. These results demonstrated that LF-NMR combined with PCA analysis has great potential in evaluate quality characteristics of HTS fillets during storage, which was confirmed previously [32][33][34]. …”
Section: Analysis Of Pcasupporting
confidence: 68%
“…LF-NMR T 2 relaxation spectra and T 2 weighted images were employed to illuminate details regarding the water dynamics and interactions with muscle structures in false abalone during wet heating ( Figure 2). Three components, representing bound water, immobilized water, and free water with each proportion ranging over 4-5%, 82-90%, and 8-21%, respectively, were determined in the T 2 relaxation data, and the content of the second component (10-100 ms) was considered to be the proportion of immobilized water within the organized muscle structures (fibers) (Shaarani, Nott, & Hall, 2006;Xia et al, 2018). Thus, the quantitative data of immobilized water in the 0-60 min thermal treatments were selected for the further analysis.…”
Section: Water Distribution Analysis By Lf-nmr and Mrimentioning
confidence: 99%
“…Furthermore, nondestructive testing (NDT) technology offers an opportunity to monitor the quality changes of food during processing (Chiou, Tsai, & Lan, 2004;Kong, Tang, Rasco, Crapo, & Smiley, 2007;Xu et al, 2016). The LF-NMR and MRI techniques have been applied to investigate the water distribution and fat content in starchy grains (Li et al, 2015), beef (Santos et al, 2014), and seafood, such as salmon (Shumilina, Ciampa, Capozzi, Rustad, & Dikiy, 2015;Wang, Xiang, Fan, Xie, & Qian, 2018), sea cucumber (Dong et al, 2017), and others by analyzing the differences in the proton spin-spin relaxation time (T 2 ) (Shao et al, 2016;Xia et al, 2018). Accordingly, an understanding of the relationship between the dynamic processes of the inner water and their significance for textual and sensory attributes during seafood cooking is urgently needed.…”
mentioning
confidence: 99%